Iranite asphalt-organic montmorillonite-nano zirconia composite modified asphalt mixture and preparation method thereof
Through the composite modification technology of Iranian rock asphalt, organic montmorillonite and nanozirconia, the high-temperature stability, low-temperature crack resistance and water stability of the asphalt mixture are improved, and the existing asphalt pavement is solved in terms of high and low temperatures and water damage. The lack of performance problems extends the service life of the road surface and reduces the maintenance costs.
Patent Information
- Application Number
- CN202411168911.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-20
AI Technical Summary
The existing asphalt pavement lacks performance in high and low temperatures and water damage, resulting in a shortened service life and an increase in maintenance costs. It is difficult for the existing technology to take into account the damage to the road surface by both high and low temperatures.
Using Iranian rock asphalt, organic montmorillonite and nanozirconium oxide composite modified asphalt mixture, the high-temperature stability, water stability, low-temperature crack resistance and wear resistance of the mixture are improved through specific raw material ratios and preparation methods. to form a synergy to enhance the overall performance of the road surface.
It significantly improves the high-temperature stability, low-temperature crack resistance and water stability of asphalt mixture, extends the service life of the road, reduces maintenance and maintenance costs, improves the economic and social benefits of the road, and enhances the adaptability of the road. and reliability.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road engineering, and in particular to an asphalt mixture compositely modified by Iranian rock asphalt-organic montmorillonite-nano zirconia and a preparation method thereof. Background Art
[0002] With the rapid development of highway construction, asphalt pavement has become the most widely used pavement form in China due to its advantages such as sufficient mechanical strength, smooth and comfortable driving, low vibration, no dust, low noise and easy maintenance. However, due to the increase in extreme weather conditions of high and low temperatures and the uncertainty of the use environment, many asphalt pavements on highways are prone to high and low temperature damage and water damage after they are built and put into operation, which greatly shortens the service life of the pavement, causing many highways to enter the overhaul or renovation period ahead of schedule, resulting in significant economic losses. The main technical means for asphalt pavements to cope with high and low temperatures today is to lay a road surface cooling coating, etc., but this technical measure cannot simultaneously take into account the damage caused to the pavement by high and low temperatures. Therefore, it is particularly important to develop a new type of modified asphalt mixture to solve the high and low temperature problems of the pavement.
[0003] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0004] The present application provides an asphalt mixture compositely modified by Iranian rock asphalt-organic montmorillonite-nano zirconia and a preparation method thereof, aiming to solve the technical problems of insufficient road performance of existing asphalt mixtures and difficulty in dealing with high and low temperature diseases and water damage.
[0005] According to one aspect of the present disclosure, an asphalt mixture is provided, which is made of the following raw materials: 100 parts of mineral material, 4-8 parts of asphalt, 1.1-1.6 parts of Iranian rock asphalt, 0.03-0.07 parts of organic montmorillonite, 0.45-0.60 parts of nano zirconium oxide, and 0.005-0.011 parts of coupling agent.
[0006] In some embodiments of the present disclosure, the asphalt mixture is made of the following raw materials: 100 parts of mineral material, 5-7 parts of asphalt, 1.2-1.4 parts of Iranian rock asphalt, 0.03-0.05 parts of organic montmorillonite, 0.52-0.59 parts of nano zirconium oxide, and 0.008-0.010 parts of coupling agent.
[0007] In some embodiments of the present disclosure, the asphalt mixture is made of the following raw materials: 100 parts of mineral material, 5.3 parts of asphalt, 1.28 parts of Iranian rock asphalt, 0.045 parts of organic montmorillonite, 0.578 parts of nano zirconium oxide, and 0.008 parts of coupling agent.
[0008] In some embodiments of the present disclosure, the asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt, and SBR modified asphalt.
[0009] In some embodiments of the present disclosure, the grading type of the mineral material is at least one of AC-13, AC-16, SMA-13, and OGFC-13.
[0010] In some embodiments of the present disclosure, the mineral material consists of coarse aggregate, fine aggregate and mineral powder.
[0011] In some embodiments of the present disclosure, the coupling agent is γ-propyltrimethoxysilane.
[0012] According to a second aspect of the present disclosure, a method for preparing an asphalt mixture is provided, comprising the following steps: (1) Prepare the raw materials according to the above raw material ratios and set aside; (2) Preparation of organic montmorillonite modifier: first dilute the coupling agent with ethanol and water to a volume percentage concentration of 1-2%, let it stand for hydrolysis for 25-35 minutes, then add organic montmorillonite and soak it for 80-100 minutes, then dry it at 70-90°C to remove water and ethanol, and obtain an organic montmorillonite modifier (with enhanced interface compatibility, improved dispersibility, improved mechanical properties, improved processing performance, and imparted with weather resistance, corrosion resistance, and flame retardancy); (3) Preparation of Iranian rock asphalt modifier and nano zirconium oxide modifier: Iranian rock asphalt and nano zirconium oxide were dried at 170-190°C for 45-55 minutes for dehydration and then used for later use; (4) Preparation of composite modified asphalt: heat the asphalt to melt at 170-190°C, add the organic montmorillonite modifier first, stir evenly, then add the Iranian rock asphalt modifier and the nano zirconium oxide modifier, stir for 40-60 minutes, and place it at 150-170°C for 35-45 minutes to swell and develop; (5) Preparation of composite modified asphalt mixture: Mix the mineral material heated to 160°C to 165°C and the composite modified asphalt and stir them evenly to obtain the composite modified asphalt mixture.
[0013] In some embodiments of the present disclosure, in step (2), the volume ratio of ethanol to water is 3:1.
[0014] In some embodiments of the present disclosure, in the step (4), the shear treatment process is: first add organic montmorillonite and stir at a shear rate of 4000-6000 r / min for 25-35 min, then add Iranian rock asphalt modifier and nano zirconium oxide modifier and shear at a shear rate of 4500-6500 r / min for 40-50 min.
[0015] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. The synergistic effect of Iranian rock asphalt, organic montmorillonite and nano zirconium oxide in this application: can significantly improve the overall road performance of asphalt mixture (such as high temperature stability, water stability, low temperature crack resistance, wear resistance, etc.); can significantly extend the service life of asphalt pavement, reduce repair and maintenance costs, and improve the economic and social benefits of roads; the modified asphalt mixture can better adapt to various complex climate and environmental conditions, and improve the adaptability and reliability of the pavement. Among them, the addition of Iranian rock asphalt can significantly improve the high-temperature rutting resistance of the mixture, reduce the rutting deformation of asphalt pavement under high temperature in summer, resist the erosion of water on asphalt pavement, and reduce the occurrence of water damage. It improves the low-temperature crack resistance of asphalt mixture to a certain extent, making the pavement less likely to crack at low temperatures; organic montmorillonite can significantly improve the physical and mechanical properties of asphalt, such as increasing the softening point and viscosity of asphalt, improving the high-temperature resistance of asphalt, and effectively improving the short-term and long-term aging properties of asphalt, extending the service life of asphalt pavement. Organic montmorillonite can improve the rheological properties of asphalt mixture, better adapt to the deformation requirements of pavement at different temperatures, and improve the road performance of the pavement; nano-zirconia added to asphalt mixture can significantly improve the wear resistance of the mixture, reduce pavement wear and peeling, and can also enhance the crack resistance of asphalt mixture to a certain extent, improve the overall strength and stability of the pavement, and the nano-scale particles of nano-zirconia can fill the tiny pores and cracks in the asphalt mixture, improve the microstructure of the mixture, and improve its density and durability.
[0016] 2. This application uses γ-propyltrimethoxysilane coupling agent solution to pre-treat the surface of organic montmorillonite, so that the organic montmorillonite can be connected with nano-zirconia in the asphalt mixture under the coupling action of the coupling agent to form a specific network connection structure, thereby enhancing the mechanical strength, impact resistance and stability of the asphalt mixture. The Iranian rock asphalt, organic montmorillonite, and nano-zirconia composite modified asphalt has a higher viscosity and can be evenly wrapped on the surface of the aggregate, thereby improving the interlocking force between the aggregates; at the same time, it has a stronger deformation recovery ability, which significantly improves the high and low temperature performance, water damage resistance and fatigue damage resistance of the asphalt mixture.
[0017] 3. The Iranian rock asphalt in this application has the characteristics of high strength, high wear resistance, and high wind and wave resistance, which can improve the high temperature performance and shear deformation resistance of asphalt. Organic montmorillonite has excellent adsorption performance, enhanced mechanical properties and good thermal stability. At the same time, nanomaterials continuously generate charges due to heat absorption, and the three can work together to achieve a good cooling effect; the compounding of the three modified materials optimizes the asphalt dosage of the asphalt mixture, forms a large amount of structural asphalt inside the mixture, and the asphalt mortar increases relatively, which weakens the intrusion of water, thereby improving the water stability of the asphalt mixture.
[0018] 4. In this application, Iranian rock asphalt can significantly improve the high temperature stability of asphalt mixture due to its high molecular weight and softening point, reduce flow and deformation at high temperature, that is, improve anti-rutting performance; organic montmorillonite can be better dispersed in asphalt due to its organic modification, improve compatibility with asphalt, thereby enhancing the mechanical properties and durability of modified asphalt; nano zirconium oxide has a high surface energy, which can improve the adhesion between asphalt and aggregate, reduce peeling and damage caused by moisture, thereby improving the mixture's ability to resist water damage, and improve the modulus and strength of asphalt. The three materials of Iranian rock asphalt, organic montmorillonite and nano zirconium oxide can work together to improve the anti-aging performance of asphalt, reduce aging caused by ultraviolet rays, heat, oxygen and other factors, improve the high and low performance of asphalt, improve the storage stability of modified asphalt, and reduce performance degradation during long-term use. DETAILED DESCRIPTION
[0019] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0020] Unless otherwise specified, the raw materials and auxiliary raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, detection methods and test methods involved are all conventional methods unless otherwise specified.
[0021] The composite modified asphalt mixture in the following embodiments includes the following preparation steps: The raw materials are prepared in the following weight proportions: 100 parts of mineral material, 4 to 8 parts of asphalt, 1.1 to 1.6 parts of Iranian rock asphalt, 0.03 to 0.07 parts of organic montmorillonite, 0.45 to 0.60 parts of nano zirconium oxide, and 0.005 to 0.011 parts of coupling agent (γ-propyltrimethoxysilane).
[0022] (1) Preparation of organic montmorillonite modifier: First, dilute γ-propyltrimethoxysilane with ethanol and water, wherein the volume ratio of water to ethanol is 1:3, and the volume percentage concentration of the γ-propyltrimethoxysilane dilution is 2%. After standing for hydrolysis for 30 minutes, add organic montmorillonite and soak for 90 minutes. Finally, dry at 80°C to remove water and ethanol to obtain the prepared organic montmorillonite modifier.
[0023] (2) Preparation of Iranian rock asphalt modifier and nano-zirconia modifier: Iranian rock asphalt and nano-zirconia were dried at 180°C for 50 min for dehydration and then used for later use.
[0024] (3) Preparation of composite modified asphalt: The asphalt was heated and melted at 180°C, and an organic montmorillonite modifier was first added, and stirred and sheared at a shear rate of 5000 r / min for 30 min. Then, an Iranian rock asphalt modifier and a nano-zirconia modifier were added, and stirred at a shear rate of 5500 r / min for 45 min. After that, the asphalt was placed at 160°C for 40 min to swell and develop.
[0025] (4) Preparation of composite modified asphalt mixture: Mix the mineral material heated to 160° C. and the composite modified asphalt and stir them evenly to obtain the composite modified asphalt mixture.
[0026] Example 1: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 4 parts of SBS asphalt, 1.10 parts of Iranian rock asphalt, 0.030 parts of organic montmorillonite, 0.450 parts of nano zirconium oxide, and 0.005 parts of coupling agent (γ-propyltrimethoxysilane).
[0027] Example 2: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 5 parts of SBS asphalt, 1.20 parts of Iranian rock asphalt, 0.035 parts of organic montmorillonite, 0.475 parts of nano zirconium oxide, and 0.006 parts of coupling agent (γ-propyltrimethoxysilane).
[0028] Example 3: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 6 parts of SBS asphalt, 1.25 parts of Iranian rock asphalt, 0.045 parts of organic montmorillonite, 0.500 parts of nano zirconium oxide, and 0.007 parts of coupling agent (γ-propyltrimethoxysilane).
[0029] Example 4: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 6.5 parts of SBS asphalt, 1.35 parts of Iranian rock asphalt, 0.050 parts of organic montmorillonite, 0.525 parts of nano zirconium oxide, and 0.008 parts of coupling agent (γ-propyltrimethoxysilane).
[0030] Example 5: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 5.3 parts of SBS asphalt, 1.28 parts of Iranian rock asphalt, 0.045 parts of organic montmorillonite, 0.578 parts of nano zirconium oxide, and 0.008 parts of coupling agent (γ-propyltrimethoxysilane).
[0031] Example 6: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 7 parts of SBS asphalt, 1.40 parts of Iranian rock asphalt, 0.055 parts of organic montmorillonite, 0.550 parts of nano zirconium oxide, and 0.009 parts of coupling agent (γ-propyltrimethoxysilane).
[0032] Example 7: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material, 7.5 parts of SBS asphalt, 1.50 parts of Iranian rock asphalt, 0.060 parts of organic montmorillonite, 0.575 parts of nano zirconium oxide, and 0.010 parts of coupling agent (γ-propyltrimethoxysilane).
[0033] Example 8: A composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 8.0 parts of SBS asphalt, 1.60 parts of Iranian rock asphalt, 0.070 parts of organic montmorillonite, 0.600 parts of nano zirconium oxide, and 0.011 parts of coupling agent (γ-propyltrimethoxysilane).
[0034] Comparative Example 1: A common asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material and 4.5 parts of SBS asphalt.
[0035] The asphalt mixtures in Examples 1-8 and Comparative Example 1 were subjected to road performance tests, including a high temperature rutting test, a low temperature beam bending test (-10°C), a freeze-thaw splitting test, and a water immersion Marshall test, to test the performance of the composite modified asphalt mixture of the present application, and to compare and analyze with ordinary asphalt without adding a modifier. The test results are shown in Table 1.
[0036] Table 1 Comparison of main performance indicators of various asphalt mixtures .
[0037] As can be seen from Table 1, the dynamic stability of the composite modified asphalt mixture is much greater than that of ordinary asphalt (Comparative Example 1), indicating that the high temperature stability of the composite modified asphalt mixture is stronger than that of ordinary asphalt; the low temperature bending strain of the composite modified asphalt mixture is much greater than that of ordinary asphalt, indicating that the composite modified asphalt mixture has stronger low temperature stability; the residual stability of the composite modified asphalt mixture is greater than that of ordinary asphalt, indicating that the composite modified asphalt mixture can still maintain better performance than ordinary asphalt after being affected by long-term high temperature and traffic loads; the freeze-thaw splitting strength ratio of the composite modified asphalt mixture is greater than that of ordinary asphalt, indicating that the composite modified asphalt mixture has higher water stability and low temperature stability.
[0038] The composite modified asphalt mixture of this application meets the relevant requirements of the Ministry of Transport's standard JTG F40-2004 "Technical Specifications for Highway Asphalt Pavement Construction". Its high temperature performance, low temperature performance, water stability and other indicators are significantly higher than those of ordinary asphalt mixtures, indicating that the composite modified asphalt mixture of this application has excellent road performance.
[0039] The present application has been described in detail above in conjunction with the embodiments; however, those skilled in the art will appreciate that, without departing from the spirit and scope of the present application, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.
Claims
1. An asphalt mixture compositely modified by Iranian rock asphalt-organic montmorillonite-nano zirconia, characterized in that: The invention is prepared from the following raw materials: 100 parts of mineral material, 4-8 parts of asphalt, 1.1-1.6 parts of Iranian rock asphalt, 0.03-0.07 parts of organic montmorillonite, 0.45-0.60 parts of nano zirconium oxide and 0.005-0.011 parts of coupling agent.
2. The asphalt mixture according to claim 1, characterized in that: The invention is prepared from the following raw materials: 100 parts of mineral material, 5-7 parts of asphalt, 1.2-1.4 parts of Iranian rock asphalt, 0.03-0.05 parts of organic montmorillonite, 0.52-0.59 parts of nano zirconium oxide and 0.008-0.010 parts of coupling agent.
3. The asphalt mixture according to claim 1, characterized in that: The invention is prepared from the following raw materials: 100 parts of mineral material, 5.3 parts of asphalt, 1.28 parts of Iranian rock asphalt, 0.045 parts of organic montmorillonite, 0.578 parts of nano zirconium oxide and 0.008 parts of coupling agent.
4. The asphalt mixture according to claim 1, characterized in that: The asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt, SBR modified asphalt, and fiber modified asphalt.
5. The asphalt mixture according to claim 1, characterized in that: The coupling agent is γ-propyltrimethoxysilane.
6. The asphalt mixture according to claim 1, characterized in that: The grading type of the mineral material is at least one of AC-13, AC-16, SMA-13, and OGFC-13.
7. The asphalt mixture according to claim 1, characterized in that: The mineral material consists of coarse aggregate, fine aggregate and mineral powder.
8. A method for preparing an asphalt mixture according to claim 1, characterized in that: The steps include: (1) Prepare the raw materials according to the raw material ratios described in claim 1 and set aside; (2) Preparation of organic montmorillonite modifier: First, dilute the coupling agent with ethanol and water to a volume percentage concentration of 1-2%, let it stand for hydrolysis for 25-35 minutes, then add organic montmorillonite and soak it for 80-100 minutes, then dry it at 70-90°C to remove water and ethanol, and obtain an organic montmorillonite modifier; (3) Preparation of Iranian rock asphalt modifier and nano zirconium oxide modifier: Iranian rock asphalt and nano zirconium oxide were dried at 170-190°C for 45-55 minutes for dehydration. (4) Preparation of composite modified asphalt: heat the asphalt to melt at 170-190°C, add the organic montmorillonite modifier first, stir evenly, then add the Iranian rock asphalt modifier and the nano zirconium oxide modifier, stir for 40-60 minutes, and place it at 150-170°C for 35-45 minutes to swell and develop; (5) Preparation of composite modified asphalt mixture: Mix the mineral material heated to 160°C to 165°C and the composite modified asphalt and stir them evenly to obtain the composite modified asphalt mixture.
9. The preparation method according to claim 7, characterized in that: In step (2), the volume ratio of ethanol to water is 3:
1.
10. The preparation method according to claim 7, characterized in that: In step (4), the shear treatment process is: firstly, organic montmorillonite is added and stirred at a shear rate of 4000-6000 r / min for 25-35 min, and then Iranian rock asphalt modifier and nano zirconium oxide modifier are added and sheared at a shear rate of 4500-6500 r / min for 40-50 min.
Citation Information
Cited By
Anti-crack asphalt mixture and preparation method thereof
CN121135232A
